Graph theory based network analysis of biofuels and related financial assets and commodities - Schererová, Barbora (2023)
This thesis provides the reader with overview of recent biofuel market and policy information, supplemented by systematic literature review of published literature dealing with biofuels and their impact on other commodities and financial assets, mainly fossil fuels and foods. In the practical part, this thesis aims to uncover these relationships by using graph theory network analysis focused on community detection in networks filtered by Minimum Spanning Tree method as well as Triangulated Maximally Filtered Graph method. The author then further provides the periodical results of Minimum Spanning Trees that provide additional information to the question of price linkages between inspected assets. The main results of this thesis are that biofuels form strongest linkages with their feedstocks, followed by other foods commodities, while these relationships are mostly heightened in periods of economic uncertainty or legislative changes. Other findings include the fact that fossil fuels form nearly independent clusters from the other assets, and are mostly influenced globally by changing interest rates and geopolitical turmoil such as increased inflation and war.